2017
DOI: 10.1186/s12888-017-1300-8
|View full text |Cite
|
Sign up to set email alerts
|

Does a child’s language ability affect the correspondence between parent and teacher ratings of ADHD symptoms?

Abstract: BackgroundRating scales are often used to identify children with potential Attention-Deficit/Hyperactivity Disorder (ADHD), yet there are frequently discrepancies between informants which may be moderated by child characteristics. The current study asked whether correspondence between parent and teacher ratings on the Strengths and Weakness of ADHD symptoms and Normal behaviour scale (SWAN) varied systematically with child language ability.MethodParent and teacher SWAN questionnaires were returned for 200 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(55 reference statements)
1
3
0
1
Order By: Relevance
“…The current study shows that there may be different contextual risks (but not necessarily unique factors) associated with clinical ADHD symptoms in preschoolers with SHA and HHA. Consistent with previous studies, teacher-reported ADHD symptoms were related to objective measurements, such as tests of inhibitory control (Jacobson et al, 2018), language ability (Gooch et al, 2017), and academic performance (Ho et al, 1996). Mannuzza et al (2002) showed in a 12-year follow-up study that children with pervasive ADHD and school-specific ADHD have a higher prevalence of antisocial disorder and greater difficulties with educational attainment and academic performance than children with home-specific ADHD.…”
Section: Resultssupporting
confidence: 86%
“…The current study shows that there may be different contextual risks (but not necessarily unique factors) associated with clinical ADHD symptoms in preschoolers with SHA and HHA. Consistent with previous studies, teacher-reported ADHD symptoms were related to objective measurements, such as tests of inhibitory control (Jacobson et al, 2018), language ability (Gooch et al, 2017), and academic performance (Ho et al, 1996). Mannuzza et al (2002) showed in a 12-year follow-up study that children with pervasive ADHD and school-specific ADHD have a higher prevalence of antisocial disorder and greater difficulties with educational attainment and academic performance than children with home-specific ADHD.…”
Section: Resultssupporting
confidence: 86%
“…Considering the school setting, most studies show that classroom teachers play a key role in providing information about a child's behavior. [2][3][4][5] Only a few studies have assessed instruments that rely on physical education teachers as a main source of information about emotional, behavioral, and/ or developmental problems in school-age children.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is possible to identify possible “cases” using SWAN algorithms, these should be treated with utmost caution. Indicative cases are reported in Supporting Information and discussed in detail elsewhere (Gooch, Maydew, Sears, & Norbury, ).…”
Section: Methodsmentioning
confidence: 99%